(untitled) (Journal of Parents and Teachers, 2014)
The article discusses the process of adaptation of adopted children, including factors that have an impact on the process. The author also provides guidelines for action in the form of advice on how to manage the adaptation process in a positive way. Finally, a reflection on this type of children is made.